Public Health in Globalization - Pokpermdee, Pongsadhorn (Journal of Health Science of Thailand, 2018)
Globalization is the phenomenon of increasing worldwide economic, market and cultural integration driven by advances in technology, telecommunication and transportation. It also has important and direct impacts on public health. Health personnel needs therefore to better understand the health implications of globalization which has both positive and negative externalities on health. Its positive effects are derived through economic growth and the wider availability of goods. In addition, it also facilitates the expansion of private sector services, medical tourism and greater patient access to health-related information. It however, has increased the risk of major infectious disease outbreaks, exacerbated health work force and brain drain issues in developing countries. Trade is another issue that inevitably affects health. Four of the current ultilateral trade agreements of the World Trade Organization-WTO carrysignificant public health implications. Recognizing its importance, international institutions such as the G8, UNITAID, Oslo Ministerial Declaration have increasingly paid greater attention to global health issues. Yet more needs arise and many countries such as Switzerland, Brazil and Singapore are preparing their systems to better respond to the rapid changes of globalization and its impact on public health. These are important lessons for Thailand which has to invest in capacity building; create more connections with stakeholders; harmonize its policy on international cooperation, trade and health; and fill the gaps in knowledge in these vital areas.